Análises reológicas no estado fresco e mecânicas de caldas de cimento portland produzidas com aditivos químicos de última geração - (:unkn) unknown (Universidade Federal do Pampa, 2015)
This paper aims to analyze the lifetime, compatibility, saturation point and the mechanical properties of three polycarboxylate based superplasticisers additives, on Portland cement mixtures. For this study, mixtures with two types of Portland cement (CP IV and CP II E) were prepared and a water/cement ratio of 0.35. The behavior of the samples were analyzed in mixtures containing different additive levels. The levels were related to the solids weight of the additive by weight of cement, ranging from 0.2% to 0.8%. Marsh Funnel and Mini abatimento tests were performed, where through the saturation curve (the point at which the additive fails to provide improvements, and start to decrease the flow) is possible to analyze compatibility and additives saturation point for each type of cement. The mixtures were analyzed at different time control, thirty minutes, one hour, two hours, three and four hours after mixing, in order to determine their useful lifetime (when the additiveis no longer providing plastic improvements to the mixture). The mechanical characteristics were determine by axial compressive and tensile tests for 7 and 28 days. After analysis of the results it is noted that the saturation point for both additives in the mixtures with CP IV was between 0.4% and 0.5%. For the mixtures with cement CP II E the saturation point was between 0.5%and0.6%. The additive 03 showed the best compatibility and lifetim e among the analyzed additives, providing plasticity gains until the last reporting period(four hours after mixing). For the axial compressive strength tests,the additive 03 showed the best results for both time control (7 and 28days). For the tensile tests on 7 and 28 days the additives 01 and 02 showed the best resistance.
Keywords: Civil engineering; Lifetime (Engineering); Resistance; Portland cement; Engenharia civil; Vida útil (Engenharia); Cimento Portland; CNPQ::ENGENHARIAS; Resistência